2012
DOI: 10.1128/jb.06385-11
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome Analysis of the Periodontopathogenic Bacterium Porphyromonas gingivalis W83

Abstract: High-density tiling microarray and RNA sequencing technologies were used to analyze the transcriptome of the periodontopathogenic bacterium Porphyromonas gingivalis. The compiled P. gingivalis transcriptome profiles were based on total RNA samples isolated from three different laboratory culturing conditions, and the strand-specific transcription profiles generated covered the entire genome, including both protein coding and noncoding regions. The transcription profiles revealed various operon structures, 5=-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 91 publications
3
39
0
Order By: Relevance
“…performed RNA-seq analysis of mRNA expression by P. gingivalis strain W83 from which 455 of the possible 463 ATCC 33277 essential genes were assayed [53]. This analysis demonstrated that 452 of 455 P. gingivalis ATCC 33277 essential genes were expressed during growth on blood agar medium (Additional file 1: Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…performed RNA-seq analysis of mRNA expression by P. gingivalis strain W83 from which 455 of the possible 463 ATCC 33277 essential genes were assayed [53]. This analysis demonstrated that 452 of 455 P. gingivalis ATCC 33277 essential genes were expressed during growth on blood agar medium (Additional file 1: Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the CRISPR-Cas and associated CAS proteins system represents a unique system that provides prokaryotic cells, as P . gingivalis , adaption and protection from host defenses [54, 55]. Down-regulation of the genes PGN_1924-Cas2, PGN_1925-Cas1 may suggest a decrease in the defensive capability of P .…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium does not ferment carbohydrates, but grows under strict anaerobic conditions using proteinaceous substrates as carbon and energy sources. Although anaerobic energy production in P. gingivalis is poorly understood, biochemical examinations (7,8), whole genome information (9,10), and transcriptome analysis (11) have led to drafts of the configurations of the entire metabolism and transport pathways.…”
mentioning
confidence: 99%